Prevalence of Dental Caries and Associated Factors among Patients Visiting a Dental Teaching Hospital of Kathmandu - Joshi, Barsha; Gautam, Suman; Joshi, Rojin; Khapung, Anju (Nepal Medical College Journal, 2023)
Dental caries is the most common oral health issue for the general population. Dental caries not only affects the quality of life but also brings economic burden to individual and society. The aim of this study was to determine the prevalence of dental caries and associated factors among patients. An analytical, cross-sectional study was conducted among the patients visiting Department of Oral Medicine of Nepal Medical College Dental Hospital of Kathmandu. The results showed that overall prevalence of dental caries was 81.6%. Dental caries among participants between 25-34 years was highest (33.1%) and more among females (84.9%). Majority of the participants used toothbrush 96.8%, while 78.3% used fluoridated toothpaste. Even though most study participants claimed to use toothbrush and fluoridated toothpaste, prevalence of dental caries was high.